PROBLEMS AND SOLUTIONS REGARDING GLOBALIZATION, LANGUAGE POLICY, AND LINGUISTIC IDENTITY IN CONTEMPORARY LINGUISTICS - Ganieva Dilshoda Izzatulla qizi; Sirojeva Navbahor Jalol qizi (ZAMONAVIY LINGVISTIKADA GLOBALIZATSIYA, TIL SIYOSATI VA LISONIY IDENTIKLIKKA OID MUAMMOLAR VA YECHIMLAR MAVZUSIDAGI XALQARO ILMIY-AMALIY ANJUMAN, 2026)
This article examines the complex relationship between globalization, language policy, and linguistic identity in contemporary linguistics. As a result of globalization processes, many languages, especially rare languages, are under threat, which reduces cultural diversity and leads to the loss of linguistic identity. The article also highlights the importance of language policy and suggests effective strategies to address these shortcomings. The authors emphasize the need to protect language rights, promote multilingualism, and support language revitalization initiatives. This study offers important solutions for the preservation and development of linguistic diversity in the era of globalization.